Is 'Easy Japanese' a Language Option? Local Responses to the Increasing Foreign Resident Population from Southeast Asia. Issue 4 (2nd October 2022) - Kusunoki, Rika; Hashimoto, Kayoko
ABSTRACT: 'Easy Japanese' ( yasashii nihongo, YN) was initially developed to disseminate information to foreign residents during emergencies after the Great Hanshin Earthquake struck Japan in 1995. Since then, YN has been promoted as a tool for communicating with foreign residents, as well as with foreign visitors to Japan in the lead-up to the 2020 Tokyo Olympics. While it has gained partial recognition among the public, local governments have tried to use YN to deal with the increasing number of temporary workers from Southeast Asia. This study examines how YN is used by municipalities in the regions where foreign residents are concentrated, and whether that usage has changed in recent years. Based on interviews with employees of municipal offices and libraries, and information on their websites, as well as relevant government documents, it reveals a lack of systematic coordination within municipalities and an absence of any initiative by the central government to implement YN. It argues that the ambiguous positioning of YN within Japan's language policy reinforces the division between Japanese people and people who do not speak Japanese, and highlights the government's limited commitment to improving the lives of foreign workers in Japan.